Challenges in Plasma Spraying of 8%Y2O3-ZrO2 Thermal Barrier Coatings on Al Alloy Automotive Piston and Influence of Vibration and Thermal Fatigue on Coating Characteristics. (2018) - Reghu, V.R; Shankar, V; Ramaswamy, Parvati
Abstract: Although Thermal Barrier Coatings (TBCs) have found extensive application in automotive engines to enhance performance and to reduce fuel consumption and pollution, challenges of obtaining uniform and consistent coatings on non-uniform and irregularly shaped components are overcome only when the coatings are deposited via robot controlled APS or EBPVD. Atmospheric Plasma Spraying (APS) is the most commonly used and relatively cost-effective method to make TBCs: but not all APS facilities are equipped with comprehensive coating accessories. In a reciprocating diesel engine, the bowl at the piston crown forms one side of the combustion chamber and includes the space between piston crown (generally 9% Si-Al alloy in light – medium duty diesel fuel vehicle) and cylinder head. To achieve maximum effective fuel spray distribution and combustion, normally the crown of the piston has complex contours. One of the many service related parameters to be monitored to reduce the innumerable faults contributing to the performance of the engine is vibration. This paper addresses the issue related with the challenges associated with the plasma spraying of consistent and adherent TBC on Al-9% Si research pistons and its complex contours by APS, subjecting the coated pistons to thermal fatigue tests and evaluation of the coating characteristics after subjecting to vibration.